'Empowerment' of adolescent girls and young women in Kinshasa: research about girls, by girls. Issue 3 (1st September 2016) - McLean, Lyndsay; Modi, Anny T.
ABSTRACT: In mid-2015, a team of 15 Congolese 'girl researchers' were recruited, trained, and mentored by the UK's Department for International Development-funded La Pépinière programme. They conducted peer-to-peer research to explore the experiences, perceptions, and aspirations of adolescent girls and young women in Kinshasa, Democratic Republic of Congo, in relation to their economic and social empowerment. In this fragile urban context, societal and personal expectations of girls and young women are high and they must carefully navigate precarious circumstances to survive economically and socially, and maintain their reputation as 'good girls'. While it is always important to ensure that development programmes are grounded in women and girls' own realities and aspirations, this is especially the case in fragile contexts where the risks are often magnified. The participatory engagement described here is a way to understand these realities and inform programmes to facilitate women and girls' own journeys of empowerment.